(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
In 1998, Namibia joined the conflict in the Democratic Republic of Congo (DRC), a conflict referred to by some as the most devastating war to have occurred since the Second World War, resulting in the death and displacement of millions of people. Involving about eight African countries, this war desta-bilised the region, resulting in it being referred to by many as ‘Africa’s First World War.’ During this war, extensive resources of nation states were allocated to warfare, instead of being channelled to-wards more productive and life-saving welfare and poverty alleviation programmes. For example, the United Nations (UN) estimates that the war in the DRC cost Namibia about N700 Million. While the involvement of Namibia attracted much criticism, it failed to attract academic research of equal measure. Of the research projects conducted, few are by Namibian researchers. There has not been a coherent descriptive account of Namibia’s involvement in this conflict. This article provides a descrip-tive account of Namibia’s involvement in this conflict while exploring and examining Namibia’s mo-tive for being involved in this devastating conflict.